Innovative Learning Media Based on Educational Game in Improving Calistung - Fathor Rozi; Arini Arini (Transformatif, 2022)
Innovative learning media can be obtained from various media, including educational game media. Games, increasingly loved by all groups, including children, should be directed towards more positive uses. This study aims to analyze and examine the use of educational games that can improve education in an elementary school institution at the first-grade level, precisely at MI Miftahul Khoir in Kotaanyar Village, Probolinggo Regency. This research uses a case study type qualitative approach by carrying out data collection techniques through data analysis, data display, and finally concluding. The study results obtained that first, at the first-grade level, MI Miftahul Khoir used educational game media to increase calistung in students. Second, the implementation of educational games was carried out with techniques; Brainstorming, Introduction to Calistung through Educational Game Media, Program Evaluation, and Continuous Improvement. The implications obtained in the use of educational games that have been well packaged can stimulate children's calistung passion, which is more increased than before when children begin to develop calistung abilities.